2015
DOI: 10.1186/s40164-016-0041-6
|View full text |Cite
|
Sign up to set email alerts
|

A systematic classification of megakaryocytic dysplasia and its impact on prognosis for patients with myelodysplastic syndromes

Abstract: BackgroundDys-megakaryopoiesis is defined as ≥10 % of dysplastic megakaryocytes in bone marrow smears by the World Health Organization. However, concordance rates for dysplastic megakaryocytes between different observers is low and, consequently, evaluation of dysmegakaryopoiesis is also often discordant.ResultsWe performed CD41 immune staining and proposed a systematic classification of dys-megakaryopoiesis on bone marrow films: (1) micro-megakaryocytes (<12 µm); (2) micro-megakaryocytes (12–40 µm) with 1 nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
2
14
0
2
Order By: Relevance
“…Histological analysis of the marrow of engrafted mice shows residual evidence of MDS-like cells, but predominantly a blast-like phenotype, consistent with transition to more malignant disease (Fig. 6d ) 55 . Lastly, examination of protein translation in human CD45+/Lin−/CD34+/CD38−/CD123+ MDS stem cells (isolated post-engraftment) shows a significant increase over the human CD45+/Lin−/CD34+/CD38−/CD123− cells (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Histological analysis of the marrow of engrafted mice shows residual evidence of MDS-like cells, but predominantly a blast-like phenotype, consistent with transition to more malignant disease (Fig. 6d ) 55 . Lastly, examination of protein translation in human CD45+/Lin−/CD34+/CD38−/CD123+ MDS stem cells (isolated post-engraftment) shows a significant increase over the human CD45+/Lin−/CD34+/CD38−/CD123− cells (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Although several murine models of MDS have been generated, the finding of dysplasia is rare and frequently subtle (reviewed in 31 ). Currently available xenotransplantation models have not been shown to replicate myelodysplasia, the essential diagnostic criterion for MDS, nor to support development of erythroand megakaryopoiesis, two of the three principal cell lines affected in MDS 32,33 . We engrafted two MDS samples with prominent dysplasia of the megakaryocytic and erythroid lineages, respectively, to evaluate dysplasia in human MDS xenografts.…”
Section: Mistrg Mice Replicate Mds Heterogeneity Myeloid Dysplasia mentioning
confidence: 99%
“…found that micromegakaryocytes were independent prognostic factors and improved predictive accuracy of the International Prognostic Scoring System-revised (IPSS-R) in their study of 422 MDS patients. 25 Our results suggest that micromegakaryocytes in de novo AML could represent a better marker for aggressive disease than the traditional WHO definition of multilineage dysplasia that takes into account dyserythropoiesis and dysgranulopoiesis, which did not affect outcome in our study. Our findings suggest that some cases currently diagnosed as AML-MRC on the basis of dyserythropoiesis and dysgranulopoiesis may not be truly biologically secondary disease and may not be appropriately classified with other AML-MRC cases defined by cytogenetics or history of MDS.…”
Section: Discussionmentioning
confidence: 49%